Growth Of black sea cucumber Holothuria atra in an integrated aquaculture system - Maureen Mercy Pattinasarany; Elizabeth Miklen Palinussa; Jolen Matakupan (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
The black sea cucumber Holothuria atra was used in integrated aquaculture with sea bass juveniles (Lates calcarifer) as the lowest and highest trophic level organism, alongside the seaweed Gracilaria sp. as an organic extractive organism. Therefore, this study aimed to assess the potential of integrated aquaculture combined with sea bass juvenile and seaweed to support the growth of the black sea cucumber. The experiment was carried out using a completely randomized design with 3 fish density treatments (50, 100, and 150 fish/m3), each integrated with 10 bags of seaweed and 4 individual black sea cucumbers. The study was conducted for 8 weeks and the fish were fed with trash fish at 10% of body weight. Water quality parameters were measured in situ every day except for TOM, ammonia, and nitrate which were measured at the beginning, middle, and end of the study. The results showed that the specific growth rate of the black sea cucumber ranged from 0.31-0.45%/day. The black sea cucumber was able to use the feed and metabolic waste produced by the culture of sea bass, showing the highest growth rate at a density of 100 fish/m3. Water quality parameters remained in ranges considered suitable for growth, except salinity. Furthermore, the black sea cucumber was found to have a strategy for adapting to fluctuations in salinity, as shown by the ability to survive at 15 ppt.Keywords:Sea bass juvenilesSeaweedSalinityTOM